Glutamine-induced signaling pathways via amino acid receptors in enteroendocrine L cell lines. (April 2020) - Nakamura, Takumi; Harada, Kazuki; Kamiya, Taichi; Takizawa, Mai; Küppers, Jim; Nakajima, Kazuo; Gütschow, Michael; Kitaguchi, Tetsuya; Ohta, Kunihiro; Kato, Tadafumi; Tsuboi, Takashi
Abstract : Glucagon-like peptide-1 (GLP-1), secreted by gastrointestinal enteroendocrine L cells, induces insulin secretion and is important for glucose homeostasis. GLP-1 secretion is induced by various luminal nutrients, including amino acids. Intracellular Ca 2+ and cAMP dynamics play an important role in GLP-1 secretion regulation; however, several aspects of the underlying mechanism of amino acid-induced GLP-1 secretion are not well characterized. We investigated the mechanisms underlying the L-glutamine-induced increase in Ca 2+ and cAMP intracellular concentrations ([Ca 2+ ]i and [cAMP]i, respectively) in murine enteroendocrine L cell line GLUTag cells. Application of L-glutamine to cells under low extracellular [Na +] conditions, which inhibited the function of the sodium-coupled L-glutamine transporter, did not induce an increase in [Ca 2+ ]i . Application of G protein-coupled receptor family C group 6 member A and calcium-sensing receptor antagonist showed little effect on [Ca 2+ ]i and [cAMP]i ; however, taste receptor type 1 member 3 (TAS1R3) antagonist suppressed the increase in [cAMP]i . To elucidate the function of TAS1R3, which forms a heterodimeric umami receptor with taste receptor type 1 member 1 (TAS1R1), we generated TAS1R1 and TAS1R3 mutant GLUTag cells using the CRISPR/Cas9 system. TAS1R1 mutant GLUTag cells exhibited L-glutamine-induced increase in [cAMP]i, whereas some TAS1R3 mutant GLUTag cells did not exhibit L-glutamine-induced increase in [cAMP]i and GLP-1 secretion. These findings suggest that TAS1R3 is important for L-glutamine-induced increase in [cAMP]i and GLP-1 secretion. Thus, TAS1R3 may be coupled with Gs and related to cAMP regulation.